Watashi, Boku and Ore An Analysis of power and solidarity dimensions in the use of pronouns of male Manga characters - Macenas, Jo Klausen E. (College of Arts and Letters, University of the Philippines Diliman, 2009)
With the growing popularity of manga and anime all over the world, people are being exposed to the Japanese language mainly through this media. Japanese continues to be a popular language studied through formal and informal means. Differences in cultural backgrounds, however, cause nuances to arise for the learners of the language. This study aims to give light to such particular distinctions in the language by analyzing the various sociocultural elements that have immense impact on Japanese. In particular, this research focuses on the role of power and solidarity dimension on pronominal selection. Combining two frameworks (Roger Brown and Albert Gilman's Power and Solidarity Principle and Dell Hymes' S-P-E-A-K-I-N-G model), the process of analysis includes identifying the relationship of the speaker and the addressee, as well as the context that surround the exchanges between the two. Results of the analysis reveal that male manga characters adhere to four factors in determining their pronounce choice: their relation to the speaker, the context in which the speech is produced, the message they want to communicate, and the impression they want to leave on the addressee.